Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Nitrogen use efficiency of monoculture and hedgerow intercropping in the humid tropics - Edwin C. Rowe; Meine Van Noordwijk; Didik Suprayogo; Georg Cadisch (Plant and Soil, 2005)

Root distributions partially explain 15N uptake patterns in Gliricidia and Peltophorum hedgerow intercropping systems - Edwin C. Rowe; Meine van Noordwijk; Didik Suprayogo; Kurniatun Hairiah; Kenneth E. Giller; Georg Cadisch (Plant and Soil, 2001)